(untitled) (Third Sector Social Economic Review, 2024)
Financial performance is an important criterion that affects the sustainability of businesses, investor confidence, and strategic decision-making processes. DuPont analysis is a tool used to evaluate companies’ financial performance. The purpose of this article is to analyze the financial performance of companies listed on the BIST Tourism Index using DuPont analysis and to compare their financial performance. The financial statements of the companies included in this study were obtained from the Public Disclosure Platform. The financial data of the companies subject to the research belong to the years 2020-2023 and are taken from the year-end financial statements. According to the research results, PKENT had the highest average return on equity, and TABGIDA had the lowest average return on equity. According to the average of all years, PETROKENT, ULAS, BAYDONER, ETILER, MARTI, DOCO, AVTUR, BIGCHEF companies can be said to use their equity more efficiently than other index companies MAALT, MERIT, AYCES, TEKTU, and TABGIDA. The average return on equity of the companies was highest in 2021 and lowest in 2020. According to these findings, companies’ equity returns on the BIST XTRZM Index have followed an unstable and fluctuating course over the years. According to the results of the research, companies should use their assets more effectively and efficiently to increase their return on equity, maintain the balance between liabilities and equity, and increase their net profit margins.